Profiling gene alterations in striatonigral neurons associated with incubation of methamphetamine craving by cholera toxin subunit B-based fluorescence-activated cell sorting - Altshuler, Rachel D.; Burke, Megan A. M.; Garcia, Kristine T.; Class, Kenneth; Cimbro, Raffaello; Li, Xuan (Frontiers in Cellular Neuroscience, 2025)
IntroductionIn both rats and humans, methamphetamine (Meth) seeking progressively increases during abstinence, a behavioral phenomenon termed “incubation of Meth craving”. We previously demonstrated a critical role of dorsal striatum (DS) in this incubation in rats. However, circuit-specific molecular mechanisms in DS underlying this incubation are largely unknown. Here we combined a newly developed fluorescence-activated sorting (FACS) protocol with fluorescence-conjugated cholera toxin subunit B-647 (CTb-647, a retrograde tracer) to examine gene alterations in the direct-pathway (striatonigral) medium spiny neurons (MSNs) associated with incubation of Meth craving.MethodsWe injected CTb-647 bilaterally into substantia nigra before or after training rats to self-administer Meth or saline (control condition) for 10 days (6 h/d). On abstinence day 1 or day 28, we collected the DS tissue from both groups for subsequent FACS and examined gene expressions in CTb-positive (striatonigral MSNs) and CTb-negative (primarily non-striatonigral MSNs). Finally, we examined gene expressions in DS homogenates, to demonstrate cell-type specificity of gene alterations observed on abstinence day 28.ResultsOn abstinence day 1, we found mRNA expression of Gabrb3 decreased only in CTb-positive (but not CTb-negative) neurons of Meth rats compared with saline rats, while mRNA expression of Usp7 decreased in all sorted DS neurons. On abstinence day 28, we found increased mRNA expression for Grm3, Opcml, and Usp9x in all sorted DS neurons, but not DS homogenate.DiscussionTogether, these data demonstrated that incubation of Meth craving was associated with time-dependent, circuit-specific, and cell type-specific gene alterations in DS involved in glutamatergic, GABAergic, opioidergic, and protein degradation signaling.